Understanding the puzzling resilience of the land share ownership in Russia: the input of Ostrom’s approach - Pascal Grouiez (Revue de la Régulation)
This paper determines how the rule-in-use on access to agricultural land affects both the size of Russian farms and the nature of land property via enforcement mechanisms. The concept of “institutional arrangements”, developed by Ostrom, is used to show that land use practices by farmers can be considered a compromise between legal land access regimes and economic and social interests of nested communities. This compromise leads to the preservation of both large-scale agricultural production units and “land-share ownership” in Orel.